2023
DOI: 10.3390/v15071421
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral Effect of Propylene Glycol against Envelope Viruses in Spray and Volatilized Forms

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is highly contagious and continues to spread worldwide. To avoid the spread of infection, it is important to control its transmission routes. However, as methods to prevent airborne infections are lacking, people are forced to take measures such as keeping distance from others or wearing masks. Here, we evaluate the antiviral activity of propylene glycol (PG), which is safe, odorless, and volatile. PG showed pronounced antiviral activity against the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
(36 reference statements)
0
1
0
Order By: Relevance
“…37 Some authors have found that polyethylene glycol (PG), which is very similar to TEG from the chemistry standpoint, increases the fluidity of the viral membrane showing a broad effect on enveloped viruses such as SARS-CoV-2. 38 Moreover, as pure TEG is a dehydrating agent, it is reasonable to think that when TEG gets in contact with microorganism membranes, it will incorporate chemisorbed and physisorbed water molecules affecting arrangement of superficial proteins.…”
Section: Introductionmentioning
confidence: 99%
“…37 Some authors have found that polyethylene glycol (PG), which is very similar to TEG from the chemistry standpoint, increases the fluidity of the viral membrane showing a broad effect on enveloped viruses such as SARS-CoV-2. 38 Moreover, as pure TEG is a dehydrating agent, it is reasonable to think that when TEG gets in contact with microorganism membranes, it will incorporate chemisorbed and physisorbed water molecules affecting arrangement of superficial proteins.…”
Section: Introductionmentioning
confidence: 99%